Modelling physiological and environmental factors regulating relative fruit set and final fruit numbers in apple trees. Issue 5 (2nd September 2020) - Lordan, Jaume; Reginato, Gabino H.; Lakso, Alan N.; Francescatto, Poliana; Robinson, Terence L.
ABSTRACT: Chemical thinning of apple ( Malus domestica Borkh.) has been practised for 50 years but it remains an unpredictable part of apple production with large variations from year to year and within years. Carbohydrate availability to support young fruitlet growth may play a significant role in apple tree response to chemical thinners, especially when the carbohydrate supply is the limiting factor for fruit growth. To address the carbohydrate component, we have tested the MaluSim model that integrates many environmental and tree physiological factors as a tool to predict chemical thinner response. The model suggests that carbon supply-to-demand variations may explain some of the great variations in thinning spray response. Relative fruit set and final fruit number per tree were affected by the carbohydrate balance within 2 days before the spray and up to 5 days after. There was a period, 15–29 days after bloom that thinners showed higher action. The greater the carbohydrate supply relative to demand, the greater the relative set and the final fruit number. This suggested that carbohydrate supply-demand balance may be a baseline for thinner responses, and that integrative modelling of these balances can be useful in understanding variation in thinning responses. Apple relative fruit set and final fruit number per tree could be modelled relatively well with consideration of initial flower density, the carbohydrate balance model, and cumulative growing degree-days since bloom.